Strategies for boosting productivity and exports of Spices from India - Biswas, Parth; Kumar, Amalendu; Pant, Devesh Kumar; Chavan, Sanket; Ali, Sk Asraful; Kumar, Dinesh (Edelweiss Applied Science and Technology, 2025)
India, often referred to as the "Land of Spices," holds a dominant position in the global spice industry, supported by its diverse climatic conditions favorable for spice cultivation. Despite its prominence, the country’s spice production is occasionally disrupted by key economic and climatic factors. This study aims to analyze the growth patterns and instability in the cultivation of major Indian spices—red chili, small cardamom, fenugreek seed, and celery seed—over a 15-year period from 2009–10 to 2023–24. Using analytical tools such as the semi-log model, Compound Annual Growth Rate (CAGR), and the Cuddy-Della Valle Index, the study evaluates trends in area, production, productivity, and exports. The findings reveal a general upward trend across all parameters for the selected spices, with the exception of cardamom, which exhibited a decline in cultivated area. A strong correlation was observed between production and exports. Nevertheless, considerable instability was noted across most spices in terms of area, production, productivity, and export. These findings highlight the need for targeted policy interventions aimed at minimizing volatility and enhancing the stability and sustainability of spice production to reduce dependence on imports and ensure self-sufficiency in the sector.